Percutaneous irreversible electroporation for treatment of small hepatocellular carcinoma invisible on unenhanced CT: a novel combined strategy with prior transarterial tumor marking - Pan, Feng; Do, Thuy; Vollherbst, Dominik; Pereira, Philippe L.; Richter, Götz Martin; Färber, Michael; Weiss, Karl Heinz; Mehrabi, Arianeb; Kauczor, Hans-Ulrich; Sommer, Christof-Matthias (Cancers, 2021)
Introduction. To explore the feasibility, safety, and efficiency of ethiodized oil tumor marking combined with irreversible electroporation (IRE) for small hepatocellular carcinomas (HCCs) that were invisible on unenhanced computed tomography (CT). Methods. A retrospective analysis of the institutional database was performed from January 2018 to September 2018. Patients undergoing ethiodized oil tumor marking to improve target-HCC visualization in subsequent CT-guided IRE were retrieved. Target-HCC visualization after marking was assessed, and the signal-to-noise ratios (SNRs) and contrast-to-noise ratios (CNR) were compared between pre-marking and post-marking CT images using the paired t-test. Standard IRE reports, adverse events, therapeutic endpoints, and survival were summarized and assessed. Results. Nine patients with 11 target-HCCs (11.1-18.8 mm) were included. After marking, all target-HCCs demonstrated complete visualization in post-marking CT, which were invisible in pre-marking CT. Quantitatively, the SNR of the target-HCCs significantly increased after marking (11.07 ± 4.23 vs. 3.36 ± 1.79, p = 0.006), as did the CNR (4.32 ± 3.31 vs. 0.43 ± 0.28, p = 0.023). In sequential IRE procedures, the average current was 30.1 ± 5.3 A, and both the delta ampere and percentage were positive with the mean values of 5.8 ± 2.1 A and 23.8 ± 6.3%, respectively. All procedures were technically successful without any adverse events. In the follow-up, no residual unablated tumor (endpoint-1) was observed. The half-year, one-year, and two-year local tumor progression (endpoint-2) rate was 0%, 9.1%, and 27.3%. The two-year overall survival rate was 100%. Conclusions. Ethiodized oil tumor marking enables to demarcate small HCCs that were invisible on unenhanced CT. It potentially allows a safe and complete ablation in subsequent CT-guided IRE.
Gesehen am 09.07.2021